Fertilizer problems ? Take sesbania ! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Fertilizer problems ? Take sesbania ! Sesbania is a leguminous plant which fixes large quantities of nitrogen. It can produce up to 200 kg of nitrogen per hectare/year when introduced as green manure in rice plantations, where it grows very rapidly....